STRATEGI KOMUNIKASI PEMASARAN PADA PRASECOND DALAM MENINGKATKAN PENJUALAN - Angela Priska; Henny Grace Enjel Naidelin Waruwu; Joseph Raja Soaloon Sihite; Muhammad Zaky (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to identify and analyze the marketing communication strategies implemented by second-hand businesses to enhance sales. Second-hand businesses, which sell used items at affordable prices, face challenges in attracting customers in a competitive market. Through qualitative research methods, data were collected from interviews with business owners and analysis of related documents. The findings indicate that effective strategies include the use of social media, word-of-mouth marketing, and promotions through giveaways. Additionally, the study found that customer engagement and increased brand exposure significantly contribute to customer loyalty and sales. Recommendations for developing more effective marketing communication strategies are also provided, including enhancing creative content and collaborating with influencers.